Commonism. A New Aesthetics of the Real. - Dockx, Nico; Bauwens, Michel; Ciancio, Giuliana; Gielen, Pascal; Laermans, Rudi; Lucchetti, Matteo; Negri, Antonio; Nomeda & Gediminas Urbonas; Otte, Hanke; Wielander, Judith (Amsterdam : Valiz, 2018)
Futurefarmers ; Gillick, Liam ; the land Foundation ; Tyfus, Dennis
neoliberalisme, commonisme, solidariteit, share-economy, peer-to-peer relationships
boek